AZÚCARES EN AGAVES (Agave tequilana Weber) CULTIVADOS EN EL ESTADO DE GUANAJUATO - Bautista-Justo, M; García-Oropeza, L.; Salcedo-Hernández, R.; Parra-Negrete, L. A. (Acta Universitaria, 2001)
The objetive of this work was to determine if the quality of Guanajuato agaves is equal to the agaves cultivated in Jalisco. A comparative study was made of the sugar content of the agave (A. tequilana Weber) cultivated in both states. Used were data of total reducing sugars (%TRS) and Brix degrees (ºBx) of raw juice samples provided by a tequilera of the region between August and December, 1998 and January and May, 2000. The data were statistically processed, applying an ANOVA analysis and a Tukey test to compare the media and the correlation between °Bx and %TRS was made. In the first period, the media %TRS from the supplier of Manuel Doblado, Gto. was 24.43 ±2.29 and did not show a significant statistical difference (p
Keywords: Array; Array; Array